PENERAPAN STRATEGI DIGITAL TASPEN BOGOR DALAM MENINGKATKAN AKSES LAYANAN PENSIUNAN - Inayatul Muthmainnah; Burhanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation in public services has become an important strategy to improve the effectiveness and accessibility of public services, including pension services. PT TASPEN (Persero) Bogor Branch Office has implemented various digital-based services to facilitate pensioners in accessing services. This study aims to analyze the implementation of TASPEN Bogor’s digital strategy in improving service accessibility for pensioners. This research employed a qualitative approach with a descriptive method. Data collection techniques were conducted through participatory observation, documentation study, and literature study. The results showed that the digital strategy was implemented through several digital service platforms, such as Andal by TASPEN, TASPEN Online Services (TOS), TASPEN Care, and TASPEN social media. The implementation of digital services provided more flexible and efficient access for pension participants, as indicated by the increase in digital service users from 85,966 participants in 2024 to 89,326 participants in 2026. However, the implementation still faced several challenges, including limited digital literacy, authentication issues, and the need for assistance in using digital services. This study shows that the success of digital transformation is determined not only by technological readiness but also by users’ readiness to utilize digital services.